Dermatomyofibroma - Orley Alvaro Campagnolo; Carlos Floriano de Morais; Marina Ochoa Ughini; Camile Mayumi Aoki; Marília Menegazzo (Sociedade Brasileira de Dermatologia, 2017)
Abstract: We report a case of dermatomyofibroma that, to our knowledge, is the second case reported in Brazil. About 100 cases have been reported worldwide. Dermatomyofibroma represents a rare, benign mesenchymal neoplasm of fibroblastic/myofibroblastic differentiation, with prolonged evolution and little or no symptoms. It most commonly occurs in young women and male children. Dermatomyofibroma can be easily confused with other clinical entities, which could lead to unnecessary treatments. Therefore, it is important that dermatologists and pediatricians suspect and start to consider this hypothesis in their diagnostic exercises.